2019
DOI: 10.1101/648451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid adaptive evolution of scale-eating kinematics to a novel ecological niche

Abstract: 31Adaptation to novel ecological niches often includes shifts in behaviors, such as new foraging 32 preferences or changes in kinematics. Investigating prey capture kinematics is an excellent way 33 to understand behavioral mechanisms underlying the origins of novel trophic specialization, in 34 which organisms begin to exploit novel resources. We investigated the contribution of 35 kinematics to the origins of a novel ecological niche for scale-eating within a microendemic 36 adaptive radiation of pupfishes o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Over 50% of the diet of the scale-eating pupfish results from high-speed (10–15 ms) strikes biting scales and protein-rich mucus from other fishes, usually generalist pupfish which make up 95% of the fish community ( Martin and Wainwright 2013a ; McLean and Lonzarich 2017 ; St. John and Martin 2019 ). This specialized niche has evolved more than 19 times in fishes across diverse environments from the deep sea ( Nakae and Sasaki 2002 ) to the Amazon basin ( Evans et al.…”
Section: The Pattern Of Trophic Novelty and Microendemic Adaptive Radmentioning
confidence: 99%
See 2 more Smart Citations
“…Over 50% of the diet of the scale-eating pupfish results from high-speed (10–15 ms) strikes biting scales and protein-rich mucus from other fishes, usually generalist pupfish which make up 95% of the fish community ( Martin and Wainwright 2013a ; McLean and Lonzarich 2017 ; St. John and Martin 2019 ). This specialized niche has evolved more than 19 times in fishes across diverse environments from the deep sea ( Nakae and Sasaki 2002 ) to the Amazon basin ( Evans et al.…”
Section: The Pattern Of Trophic Novelty and Microendemic Adaptive Radmentioning
confidence: 99%
“…This is particularly striking given that scale-eating involves high-speed ramming strikes on pupfish prey, an escalation of typical aggressive behavior, whereas consuming snails does not require high-speed strikes nor conspecific aggression, only increased stability of oral and pharyngeal jaws ( Hernandez et al. 2017 ; St. John and Martin 2019 ). These results do not support the aggression hypothesis and indicate that both specialists may exhibit high levels of aggression due to trophic specialization or due to the indirect effects of selection on other traits ( St. John et al.…”
Section: How Can Behavioral Studies Inform the Origins Of Novel Ecolomentioning
confidence: 99%
See 1 more Smart Citation
“…Found in the benthic littoral zone of each lake, all three species forage within the same benthic microhabitat; indeed, no habitat segregation has been observed in 14 years of field studies. Originating less than 10,000 years ago (based on geological age estimates for the lakes: (49)), the functional and trophic novelty harbored within this radiation is the product of exceptional rates of craniofacial morphological evolution (5053). Furthermore, species boundaries persist across multiple lake populations, despite persistent admixture among species (54, 55).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers thought that hybridization was an evolutionary dead end [1], because hybrids were more often observed to be less healthy and ecologically adapted than either parent species, and tended to be sterile [2][3][4][5][6][7]. However, others indicated that hybridization can provide an important source of genetic variation on which selection might act and that its adaptive role was more widespread [8][9][10][11][12][13][14][15][16]. The survival and adaptation of F1 hybrids is the first and most important step in hybrid speciation and is affected by both genetic and ecological challenges.…”
Section: Introductionmentioning
confidence: 99%